Особенности гнездования куликов и чаек на островах Молочного лимана (Азовское море) - Филонов, К.П.; Лысенко, В.И.; Сиохин, В.Д. (Вестник зоологии, 1974)
Breeding colonies of birds were observed on islands of Molochny estuary for 1969-1972. Ecological peculiarities of Limicolae and Lari reproduction were traced. The dates of reproduction start, egg quantity in a clutch, periods of nestlings hatching were determined for Charadrius alexandrinus L., Tringa totanus L., Recurvirostra avosetta L., Larus argentatus Pont., L. genci Breme, Gelochelidon nilotica Gm., Sterna hir-Tundo L., S. albifrons Pall. and S. sandvicensis Lath.